2022
DOI: 10.1007/s00217-022-04105-9
|View full text |Cite
|
Sign up to set email alerts
|

Hyperlipidemia control using the innovative association of lupin proteins and chitosan and α-cyclodextrin dietary fibers: food supplement formulation, molecular docking study, and in vivo evaluation

Abstract: Hyperlipidemia control by using the innovative association of lupin proteins and chitosan and α-cyclodextrin dietary fibres: food supplement formulation, molecular docking study and in vivo evaluation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…Lupin protein hydrolysates (LPHs) (100 mg/kg) orally administered for 12 weeks showed significant hypocholesterolemic effects in Western diet-fed ApoE −/− mice (a commonly used atherosclerotic mouse strain, serving as a spontaneous model of atherosclerosis that most resembles the atherosclerotic process in humans) through the modulation of LDL receptor (LDLR) and PCSK9 pathways [ 59 ] and further achieved the effects of alleviating oxidative stress and aortic inflammation, preventing the early stages of atherosclerosis [ 58 ]. In addition, a combination of lupin proteins (LPs) with natural macromolecules, such as chitosan (CH) and α-cyclodextrin (α-CD), promised a superior therapeutic effect in a hyperlipidemic rat model (acute hyperlipidemia induced by intraperitoneal injection of 1 g/kg body weight of Poloxamer 407 in nocturnally fasted rats) [ 60 ].…”
Section: Pulse Proteins and Their Hydrolysates For Improving Metsmentioning
confidence: 99%
“…Lupin protein hydrolysates (LPHs) (100 mg/kg) orally administered for 12 weeks showed significant hypocholesterolemic effects in Western diet-fed ApoE −/− mice (a commonly used atherosclerotic mouse strain, serving as a spontaneous model of atherosclerosis that most resembles the atherosclerotic process in humans) through the modulation of LDL receptor (LDLR) and PCSK9 pathways [ 59 ] and further achieved the effects of alleviating oxidative stress and aortic inflammation, preventing the early stages of atherosclerosis [ 58 ]. In addition, a combination of lupin proteins (LPs) with natural macromolecules, such as chitosan (CH) and α-cyclodextrin (α-CD), promised a superior therapeutic effect in a hyperlipidemic rat model (acute hyperlipidemia induced by intraperitoneal injection of 1 g/kg body weight of Poloxamer 407 in nocturnally fasted rats) [ 60 ].…”
Section: Pulse Proteins and Their Hydrolysates For Improving Metsmentioning
confidence: 99%
“…Their housing environment was meticulously regulated, maintaining a 14-hour light and 10-hour dark cycle, with precise control over temperature (23 ± 3°C) and humidity parameters (60 ± 10 %). Moreover, the mice were provided ad libitum access to standard rodent pellet diets and water, ensuring their consistent exposure to standardized environmental conditions throughout the experimentation (Elmowafy et al, 2022).…”
Section: In Vivo Investigationmentioning
confidence: 99%
“…After 24-hour interval, blood specimens were judiciously retro-orbitally collected and subsequently employed for the comprehensive assessment of various lipid parameters. On the terminal day of the experimental protocol, the animals were ethically euthanized in strict accordance with IAEC protocol to facilitate subsequent in-depth histopathological analyses (Elmowafy et al, 2022; Lee et al, 2006).…”
Section: In Vivo Investigationmentioning
confidence: 99%
“…It is high in protein, fiber, and bioactive substances such as carotenoids, antioxidants, and phytoestrogens (Albuja‐Vaca et al., 2019). Substantial research has shown that intake of lupin‐based food products causes a decline in low‐density lipoprotein amounts (Boukid & Pasqualone, 2021), plasma cholesterol and triglycerides (Elmowafy et al., 2022), and blood pressure (Lee et al., 2009). Adding of lupin fiber to the diet led in positive changes in blood lipids, suggesting that it may be effective in lowering the risk of coronary heart disease (Belski, 2012).…”
Section: Introductionmentioning
confidence: 99%